Extraction of flavonoids in pomelos’ peels using Box-Behnken response surface design and their biological activities - Truong Ngoc Quynh Phuong; Pham Van Hung; Nguyen Thi Lan Phi (Vietnam Journal of Science, Technology and Engineering, 2021)
The objectives of this study were to optimize the extraction conditions of flavonoids from the pomelo peel using the Box-Behnken response surface methodology and to investigate the chemical composition and biological activities of the extracts from three different pomelo species under optimized extraction conditions. Three extraction condition factors of were varied, including the solid-solvent ratio (1/15-1/45 g/ml), temperature (30-60oC), and time (20-60 min), which affected the efficiency of the total flavonoid content (TFC). The high R2 coefficient of 0.93 indicated that the experimental data obtained in this study fit well to a second-order polynomial using multiple regression analysis. The maximum TFC extracted from the pomelo peel was 6.0 mg/g (dried basis, db), which was obtained using Derringer’s desired function methodology under the following optimum conditions: a solid-solvent ratio of 1/44 g/ml, temperature of 30.7oC, and time of 34.6 min. The results also indicated that the Tan Trieu pomelo peel had the highest TFC and naringin concentration followed by the Nam Roi and Duong Hong pomelo peels, whereas the Nam Roi pomelo peel had a higher hesperidin concentration than the others. The extracts of the pomelo peels exhibited strong antioxidant activities with low IC50 values. However, these extracts showed only a slight effect on cancer cells, including lung cancer and breast cancer, when tested at 100 µg/ml.